Photoelectrocatalytic H2 evolution from integrated photocatalysts adsorbed on NiO - Põldme, Nils; O'Reilly, Laura; Fletcher, Ian; Portoles, Jose; Sazanovich, Igor V.; Towrie, Michael; Long, Conor; Vos, Johannes G.; Pryce, Mary T.; Gibson, Elizabeth A. (Chemical science (Cambridge), 2019)
A new approach to increasing the faradaic efficiency of dye-sensitised photocathodes for H 2 evolution from water, using integrated photocatalysts, furnished with ester groups on the peripheral ligands, [Ru(decb) 2 (bpt)PdCl(H 2 O)](PF 6 ) 2 ( 1 ) and [Ru(decb) 2 (2,5-bpp)PtI(CH 3 CN)](PF 6 ) 2 ( 2 ), (decb = 4,4′-diethylcarboxy-2,2′-bipyridine, bpp = 2,2':5′,2′′-terpyridine, bpt = 3,5-bis(2-pyridyl)-1,2,4-triazole) is described. Overall, 1 |NiO is superior to previously reported photocathodes, producing photocurrent densities of 30–35 μA cm −2 at an applied bias of −0.2 V vs. Ag/AgCl over 1 hour of continuous white light irradiation, resulting in the generation of 0.41 μmol h −1 cm −2 of H 2 with faradaic efficiencies of up to 90%. Furthermore, surface analysis of the photocathodes before and after photoelectrocatalysis revealed that the ruthenium bipyridyl chromophore and Pd catalytic centre ( 1 ) were photochemically stable, highlighting the benefits of the approach towards robust, hybrid solar-to-fuel devices.